Uma análise histórica do desenvolvimento da probabilidade e a utilização de materiais concretos para seu ensino - Paulo, Francisco Ferreira de. (2013)
The theme that sometimes we study A Historical Analysis of the Development and Use of Materials Probability concrete For your Teaching demand, considering the wealth of options, prioritize research with concrete materials and easy access to the student and the teacher. So we did a brief history of the origin and theories necessary for the calculation of probability applications involving gambling with coins, dice and playing cards, thus leading to a more concrete and useful way for meaningful student learning.